On Vehicle Pitch Estimation via solid-state LIDAR. Issue 2 (2020) - Selmanaj, Donald; Corno, Matteo; Panzani, Giulio; Savaresi, Sergio M.
Abstract: Solid-state LIDAR technology has recently emerged, allowing for smaller and more affordable devices. In the present work, we investigate the possibility of using a vehicle mounted solid-state LIDAR to estimate the vehicle pitch and heave dynamics. We present and compare two approaches: a model-based estimation and a data driven algorithm. The algorithms are tested on an instrumented vehicle. The experimental results show that the data-driven approach outperforms the model-based estimation in estimating pitch caused both by accelerations and braking and by road disturbances.